KETERAMPILAN MEMECAHKAN MASALAH FARAID DITINJAU DARI KEMAMPUAN MATEMATIS MAHASISWA - Kamulia, Aknis Ayu Utami; Tohir, Mohammad; Safitri, Helvi Dian Safitri Dian; Rosyidah, Ummi (Kadikma, 2022)
The phenomenon experienced by students is their inability to determine the parts of the term Ashabul Furudh. This material is indeed difficult to understand, in addition to the many parts that must be known, it is also necessary to understand the fraction material. This is where one of the functions of mathematics in life is included in calculating inheritance. This study aims to examine students' thinking patterns in solving faroidh problems. In this study using a qualitative descriptive method. The subjects in this study were students of Tadris Mathematics semester VI. The results of this study indicate that overall students are included in the creative category because they are able to meet the four categories of creative thinking abilities that have been determined, namely fluency, flexibility, detail, and sensitivity. The high group subjects had very good creative thinking, the medium group subjects had good creative thinking and for the lower group subjects had moderate creative thinking.